2013
DOI: 10.1016/j.neurobiolaging.2012.10.009
|View full text |Cite
|
Sign up to set email alerts
|

A novel phosphorylation site mutation in profilin 1 revealed in a large screen of US, Nordic, and German amyotrophic lateral sclerosis/frontotemporal dementia cohorts

Abstract: Profilin 1 is a central regulator of actin dynamics. Mutations in the gene profilin 1 (PFN1) have very recently been shown to be the cause of a subgroup of amyotrophic lateral sclerosis (ALS). Here, we performed a large screen of US, Nordic, and German familial and sporadic ALS and frontotemporal dementia (FTLD) patients for PFN1 mutations to get further insight into the spectrum and pathogenic relevance of this gene for the complete ALS/FTLD continuum. Four hundred twelve familial and 260 sporadic ALS cases a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
62
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 71 publications
(66 citation statements)
references
References 34 publications
3
62
0
1
Order By: Relevance
“…Specifically, in 75 out of the 301 index patients, a Southern blot-confirmed C9orf72 hexanucleotide repeat expansion (HRE) was detected (figure 1). Thirty-seven index patients turned out to carry non-synonymous variants in SOD1 (variants with a minor allele frequency (MAF) 1:10 000 or lower (according to the ExAC dataset), except for the known pathogenic p.D91A mutation with MAF of 1:891), and further mutations were found in TARDBP (three pedigrees detected with two different mutations14), in FUS (eight pedigrees detected with six different mutations15 16), in OPTN (one pedigree detected with one mutation17), in PFN1 (one pedigree detected with one mutation18), in  SETX (two pedigrees detected with two different mutations19) and in  ALS2 (one pedigree detected with one mutation20). …”
Section: Resultsmentioning
confidence: 99%
“…Specifically, in 75 out of the 301 index patients, a Southern blot-confirmed C9orf72 hexanucleotide repeat expansion (HRE) was detected (figure 1). Thirty-seven index patients turned out to carry non-synonymous variants in SOD1 (variants with a minor allele frequency (MAF) 1:10 000 or lower (according to the ExAC dataset), except for the known pathogenic p.D91A mutation with MAF of 1:891), and further mutations were found in TARDBP (three pedigrees detected with two different mutations14), in FUS (eight pedigrees detected with six different mutations15 16), in OPTN (one pedigree detected with one mutation17), in PFN1 (one pedigree detected with one mutation18), in  SETX (two pedigrees detected with two different mutations19) and in  ALS2 (one pedigree detected with one mutation20). …”
Section: Resultsmentioning
confidence: 99%
“…PFN1 mutations have been reported to be a rare cause of familial ALS 4 7. The PFN1 E117G variant has been also found in sporadic ALS patients, but its presence in numerous control individuals has raised concerns about its role in disease 4–11.…”
Section: Discussionmentioning
confidence: 99%
“…Exome sequencing has revealed 8 mutations in the profilin1 gene in familial and sporadic ALS cases in the United States, Europe and China; (A20T, C71G, G118V, M114T, E117G, T109M, R136W, Q139L) (Figure 1B) [4143]. A study of 10 fALS and 540 sALS patients in China reported one nonsynonymous mutation (R136W) in one early-onset sporadic ALS patient [44].…”
Section: Profilin1 and Alsmentioning
confidence: 99%
“…They also found a synonymous mutation (L88L) in a late-onset sALS patient, which would not have caused a mutation of the profilin1 protein, but may affected its expression since its RNA sequence changed by one nucleotide base. Although research teams outside of the United States and Europe have searched for profilin1 mutations in their local fALS patients, these studies did not identify any abnormalities, suggesting that profilin1 mutations may not be uniformly distributed across ALS patient populations in different geographical areas [41, 4351,55]. …”
Section: Profilin1 and Alsmentioning
confidence: 99%